KAJIAN DAN EVALUASI PEMUSTAKA UNIT PELAKSANA JASA PDII-LIPI DI SERPONG - Rahartri, Rahartri (BACA: Jurnal Dokumentasi dan Informasi, 2018)
The study aims to evaluate the number of UPJ PDII-LIPI Serpong visitors from 2010 - 2016. The study was carried out descriptively, with data sources obtained from visitor books and UPJ PDII-LIPI Serpong monthly reports. More in-depth information was explored from the visitors regarding factors that influenced the interest of visitors. Based on the results of the analysis, it can be concluded that: (1) total visitors to UPJ PDII-LIPI Serpong from 2010 - 2016 are as many as 2331 people (41,8%) from the Puspiptek area (LIPI, BPPT, BATAN, PPIT, KLHK; and 58,2% from outside the Puspiptek region (school students, university students, the general public, industry, and institutions outside the Puspiptek area); (2) visitors from the Puspiptek area are dominated by LIPI followed by BPPT, BATAN, PPIT, and KLHK. While visitors from outside the Puspiptek area are dominated by school students, then followed by university students, the general public, industry, and institutions outside Puspiptek area; (3) the purposes of visitors to UPJ PDII-LIPI Serpong are to get references, do observations, literature studies, comparative studies, reading, browsing internet, working on research assignments/reports, and consulting about libraries; (4) the decreasing a number of visitors at UPJ PDII-LIPI Serpong.